TRANSITIVITY ANALYSIS OF TENTH GRADE STUDENTS’ RECOUNT TEXTS - Dessy Senjawati (Journal of English and Education, 2016)
The focus of this study is to investigate the students’ recount texts based on its criteria and to investigate the students’ problems in writing the texts. This research employed qualitative research design with a case study approach. The data were six pieces of recount text written by tenth grade students of private school in Bandung. It is different from other previous studies which took the data on students’ first texts. In this research, the students were assigned to write three drafts with two times feedback from the teacher, then their final texts were used as the main data. The data analysis was carried out by identifying the students’ recount texts in terms of purpose, linguistic features (using Transitivity system), schematic structure of recount text criteria and also the students’ problems in writing the texts. The findings show that all students were aware about the social purpose of recount text and how recount text should be written based on its criteria, appropriate schematic sructure and linguistic features. Moreover, the students’ texts consist of material, mental, relational, verbal and existential processes which fulfill the criteria of recount text’s linguistic features. However, the fulfillment of recount text’s criteria was still inadequate for some students. Some students still faced some problems, especially grammatical structure. Moreover, the result of problem analysis shows that there are three most frequent grammatical mistakes in students’ texts: plural, past tense and article. Therefore, teachers should be more aware in students’ problems in writing and also should help the students to enhance their writing skills.